Windows 10 : the missing manual - Pogue, David (Missing manual., 2018)
Windows 10 hit the scene in 2015 with an all-new web browser (Edge), the Cortana voice assistant, and universal apps that run equally well on tablets, phones, and computers. Now, the Creators Update brings refinement and polish to Windows 10--and this jargon-free guide helps you get the most out of this supercharged operating system. Windows 10: The Missing Manual covers the entire system, including all the new features, like the three-column Start menu, the extensions in the Microsoft Edge browser, Paint 3D, and live game broadcasting. You'll learn how to: Explore the desktop, including File Explorer, Taskbar, Action Center, and Cortana Work with programs and documents, Windows starter apps, the Control Panel, and 3D apps Connect with Edge and email Beef up security and privacy Set up hardware and peripherals, including tablets, laptops, hybrids, printers, and gadgets Maintain computer health with backups, troubleshooting tools, and disk management Learn about network accounts, file sharing, and setting up your own small network Written by David Pogue--tech critic for Yahoo Finance and former columnist for The New York Times --this updated edition illuminates its subject with technical insight, plenty of wit, and hardnosed objectivity.